Interleukin-3-dependent expression of the c-myc and c-fos proto-oncogenes in hemopoietic cell lines. - Conscience, J F (1986)
Using Northern blot analysis the expression of several proto-oncogenes was studied in established lines of mast cell precursors. Upon removal of interleukin-3 (IL-3) from the culture medium, factor-dependent cells stop dividing. During the first 7 h, however, normal amounts of total cellular mRNAs are maintained, and this is reflected in unchanged levels of several transcripts, such as actin, c-Ha-ras and c-fes. In contrast, within 1.5 h of IL-3 removal, the levels of c-myc and c-fos mRNAs decrease drastically and addition of IL-3 at that stage quickly induces back the levels found in actively growing cultures. In factor-independent cells, which proliferate actively even in the absence of IL-3, high levels of c-myc and c-fos transcripts are maintained in the absence of growth factor. In cells arrested by serum starvation, addition of 10% serum induces massive amounts of c-fos transcripts, but not of c-myc, and cell proliferation is not restored. The data suggest that the c-myc and c-fos proto-oncogenes play an important role in mediating the multiple effects of IL-3 on hemopoietic progenitor cells.